Chapter Languages of the Middle Andes in areal-typological perspective Emphasis on Quechuan and Aymaran. - Adelaar, Willem F.H (De Gruyter, 2012)
Among the indigenous languages of the Andean region of Ecuador, Peru, Bolivia, northern Chile and northern Argentina, Quechuan and Aymaran have traditionally occupied a dominant position. Both Quechuan and Aymaran are language families of several million speakers each. Quechuan consists of a conglomerate of geo-graphically defined varieties, traditionally referred to as Quechua "dialects", not-withstanding the fact that mutual intelligibility is often lacking. Present-day Aymaran consists of two distinct languages that are not normally referred to as "dialects". The absence of a demonstrable genetic relationship between the Quechuan and Aymaran language families, accompanied by a lack of recognizable external gen-etic connections, suggests a long period of independent development, which may hark back to a period of incipient subsistence agriculture roughly dated between8000 and 5000 BP (Torero 2002: 123-124), long before the Andean civilization attained its highest stages of complexity.